Water Boiling Celery Affects Blood Pressure in Elderly with Hypertension - Erni Tri Indarti; Lexy Oktora Wilda; Yiyin Nuvitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Backgroud One of the degenerative diseases that become a health problem in the world is hypertension. High blood pressure is commonly found in elderly patients. The cause of hypertension in the elderly is losing the elasticity of blood vessels. Purpose The purpose of this research to determine the influence of water boiling celery against blood pressure in the elderly with hypertension. Metods Design research using pre experiment with One group approach pre-post test design. Population of all elderly hypertension in Posyandu elderly Bruno village Ngliman Sawahan District Nganjuk with a total of 24 elderly. Held on 2-8 March 2020. Sample 24 respondents with Total Sampling. An independent variable is the boiling of celery water, and a blood pressure dependent variable using a sphygmomanometer. Analysis used the Wilcoxon Signed Rank test through the program SPSS version 16 with α = 0.05. Results The results of the study were obtained from 24 respondents of blood pressure in the elderly before being given the boiling water of celery nearly half the mild category, which is 11 respondents (46%). Blood pressure in the elderly after being given the boiling water of celery almost entirely mild category, which is 20 respondents (83.4%). The Wilcoxon Signed Rank test obtained p value 0.035 ≤ α = 0.05, Ha was accepted and there was an influence of water-giving celery for blood pressure in the elderly with hypertension. Concluion In this case the boiling water of celery can make one of complementary therapies in lowering blood pressure, especially against the elderly. In addition to the water of celery decoction can be a non-pharmacological therapy, so that someone who is experiencing high blood pressure pain or hypertension does not necessarily depend on the drug in lowering high blood pressure.